Imagining climate change: The role of implicit associations and affective psychological distancing in climate change responses - Leviston, Z.; Price, J.; Bishop, Brian John (John Wiley and Sons Ltd, 2014)
Negative climate change imagery is often criticised on the grounds that it provokes and promotes disempowering responses and psychological distancing. We investigated people's associations with climate change, and their affective content on multiple dimensions, through two studies. In Study 1, we administered an image-elicitation task to 2502 people across Australia to examine the mental images most commonly associated with climate change. We used these common responses from the image-elicitation task to compile 82 actual images. In Study 2, these images were presented to participants at a series of four workshops (N=52). Participants selected the images they most closely associated with climate change, rated them for affective content on an emotion circumplex, and later discussed evocative images in small groups. The findings suggest (i) a significant proportion of people struggle to form concrete associations; (ii) common associations are typically psychologically distant and iconographic, but some national-level impacts are also salient; and (iii) associations with climate change impacts differ in their affective content: Specifically, associations related to drought and denuded landscapes provoke lower arousal, whereas associations related to disasters and extremes provoke higher arousal. The importance of considering motivated reasoning and multi-dimensional affect in the psychological distancing of climate change is discussed. © 2014 John Wiley & Sons, Ltd.